1999
DOI: 10.1177/106907279900700106
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Rating Scale for Assessing Career Choice Appropriateness in Adolescence

Abstract: This article describes a study to construct and validate a rating scale to assess appropriateness of career choices of 143 high school students. Test-retest reliability coefficients for the rating scale scores were in the .80s and .90s. Intercorrelations of teacher and counselor ratings were in the .50s and .60s. Rating scale scores correlated mostly in the .30s with an objective testing method of assessing appropriateness of students' career choices, based on ACT Career Planning Program (1985) scores. Sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The coefficient alpha was .95 for the seven-item scale. Westbrook, Sanford, and Waters (1999) investigated the psychometric characteristics of the counselor rating scale to assess appropriateness of career choices of 143 high school students. The results showed that teacher and counselor ratings ranged from .59 to .66.…”
Section: Methodsmentioning
confidence: 99%
“…The coefficient alpha was .95 for the seven-item scale. Westbrook, Sanford, and Waters (1999) investigated the psychometric characteristics of the counselor rating scale to assess appropriateness of career choices of 143 high school students. The results showed that teacher and counselor ratings ranged from .59 to .66.…”
Section: Methodsmentioning
confidence: 99%